2014
DOI: 10.1128/jcm.00288-14
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Two Commercially Available Assays (Abbott RealTi m e HIV-1 and Roche Cobas AmpliPrep/Cobas TaqMan HIV-1 Version 2.0) To Quantify Low HIV-1 RNA Levels (<1,000 Copies/Milliliter): Comparison with Clinical Samples and NIBSC Working Reagent for Nucleic Acid Testing Assays

Abstract: Concordance between molecular assays may be suboptimal at low HIV-1 viremia levels (<1,000 copies/ml); therefore, it may be difficult to define and compare virologic endpoints for successful and failed therapy. We compared two commercial assays (the Abbott RealTime HIV-1 and the Roche Cobas AmpliPrep/TaqMan HIV-1 version 2.0) for their ability to detect and quantify low viral loads. A comparison was performed using 167 residual clinical samples (with values ranging from "not detected" to 1,000 copies/ml, as me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
2
25
1
Order By: Relevance
“…This result is consistent with several studies that tested samples in parallel with these two assays and found that Taqman-2 has greater sensitivity for detecting low-level HIV RNA [22,23].…”
Section: Discussionsupporting
confidence: 81%
“…This result is consistent with several studies that tested samples in parallel with these two assays and found that Taqman-2 has greater sensitivity for detecting low-level HIV RNA [22,23].…”
Section: Discussionsupporting
confidence: 81%
“…There are two FDA-approved HIV-1 real-time assays that are used by most clinical laboratories, the Cobas AmpliPrep/Cobas TaqMan HIV-1 test (Roche Molecular Systems Inc., Pleasanton, CA) and the RealTime HIV-1 assay (Abbott Molecular). Studies have compared the performance characteristics of these assays (17)(18)(19); more recent reports (20)(21)(22) have assessed the performance characteristics of the Aptima assay and shown excellent overall performance in detection and accurate quantification of all the major HIV-1 subtypes, and viral load values agreed well with those of other established assays. Our results confirmed these findings; the Aptima assay had good linearity over the quantification range of the assay tested, and plasma viral load results were highly correlated with the RealTime results (R 2 ϭ 0.99), with a comparable coefficient of variance of Ͻ5.5%.…”
Section: Discussionmentioning
confidence: 90%
“…The NucliSens v2.0 assay has been shown to be less precise than the Roche Cobas AmpliPrep/Cobas TaqMan v2.0 (15) and Versant bDNA (8) assays. The RealTime assay was reported to have excellent intra-assay and interassay reproducibility (10% variability) at low viral loads (12) and to be more accurate than Roche assays (16,17), although greater variability (30%) at a high viral load (6 log copies/ml) (12) and a tendency to underquantify lowviremic samples have been reported (18)(19)(20). In a recent large international collaborative study using 4,221 paired samples, the overall correlation and concordance between several viral load assays (including the RealTime assay) were found to be lower at low viral loads than at higher loads (21 and high correlation values, with overall minimal mean viral load differences between the two assays (0.04 log copies/ml) (8,22).…”
Section: Discussionmentioning
confidence: 99%